Viruses as therapeutic and infectious agents - Pereira, Sara Raquel do Souto (2018)
The present study is divided into two parts: the first part focuses on the use of viruses, specifically bacteriophages as an antimicrobial therapy, and the second part focuses on an epidemiological study conducted in partnership with the Clinical Laboratory Avelab, in which the prevalence of hepatitis A and C viruses between 2002 and 2012 is demonstrated. Enterobacter cloacae is part of the normal flora of the gastrointestinal tract of 40 - 80% of people. This opportunistic microorganism is capable of causing infection in debilitated and hospitalized patients, such as urinary tract infections (UTI) associated with the use of urethral catheters. E. cloacae is resistant to a broad number of antibiotics therefore infections caused by this bacterium are difficult to control. Phage therapy may be a useful tool to control infections caused by antibiotic resistant strains. Three previously isolated phages E-2, E-3 and E-4 produced on E. cloacae were used to examine survival and host-phage dynamics in a buffer solution and in urine in order to evaluate their ability to treat UTI. The survival was determined in phosphate buffered saline (PBS) through quantification by soft agar overlay technique. The host-phage dynamics was characterized in Tryptic Soy Broth (TSB) medium and in human urine samples. The concentration of E-2 decreased by two orders of magnitude in the first 105 days. E-3 was not detectable after 160 days. E-4 concentration only decreased by one order of magnitude after 255 days. The results show that the growth of the E. cloacae was inhibited by the three phages, resulting in a decrease of ≈ 3 log after 4 - 10 h of incubation. The use of cocktails with two or three phages was significantly more effective, namely the phage cocktail E-2/E-4, with reductions of ≈ 4 log after only 2 hours of treatment. In urine, although the phage cocktail E-2/E-4 was less efficient in E. cloacae inactivation than in PBS, the inactivation was effective, bacterial reduction of 2.3 log after 4 h of incubation. Phages E-2, E-3 and E-4 showed an efficient inactivation of E. cloacae, namely when used as phage cocktails, being potential candidates as agents for the control of nosocomial urinary tract infections caused by Enterobacter cloacae. Hepatitis A is a common viral liver disease and brings serious health and economic problems as its epidemiologic pattern changes over time. National serosurveys from developed countries have indicated a decline in HAV (hepatitis A virus) seroprevalence over time due to the improvement of economic and sanitation levels. The hepatitis A virus (HAV) immunity rate was surveyed throughout an eleven-year period by sex and age group in Aveiro District. Hepatitis C virus (HCV) is a major cause of liver disease worldwide and causes substantial morbidity and mortality. The common absence of symptoms associated leads to uncertainty to the geographic distribution of this disease. In the absence of a vaccine and effective treatment, prevention is extremely important, especially for at risk groups. The immunity rate of hepatitis A and the infection rate of Hepatitis C were surveyed over a period of eleven years by sex and age group in the district of Aveiro. In this retrospective study, blood samples from patients in ambulatory regime from the Laboratory of Clinical Analysis Avelab, were analyzed for the presence of antibodies against antigens of HAV and HCV using a chemiluminescence immunoassay. The HAV immunity was 60%. The immunity was age dependent (p <0.05) but no significant differences were noted between sexes or during the study period (p> 0.05). About 4% of patients had anti-HCV antibodies. HCV infection was age and gender-dependent (p <0.05) and decreased during the study period (p <0.05). The results presented in this study indicate that the immunity for HAV in young patients is low and may indicate a greater impact of the disease in the future. Regarding HCV infection is concluded that middle-aged men are more affected by HCV than women which may indicate that this group is more prone to risky behavior. In addition, the reduction of infection rate throughout the study period may indicate a decrease in exposure to risk factors.